Working musicians : labor and creativity in film and television production - Taylor, Timothy Dean (Duke University Press, 2023)
"In Working Musicians Timothy D. Taylor offers a behind-the-scenes look at the labor of the mostly unknown composers, music editors, orchestrators, recording engineers, and other workers involved in producing music for films, television, and video games. Drawing on dozens of interviews with music workers in Los Angeles, Taylor explores the nature of their work and how they understand their roles in the entertainment business. Taylor traces how these cultural laborers have adapted to and cope with the conditions of neoliberalism, as over the past decade, their working conditions have become increasingly precarious. Digital technologies have accelerated production timelines and changed how content is delivered, while new pay schemes have emerged that have transformed composers from artists into managers and paymasters. Taylor demonstrates that as bureaucratization and commercialization affect every aspect of media, the composers, musicians, music editors, engineers, and others whose soundtracks excite, inspire, and touch millions face the same structural economic challenges that have transformed American society, concentrating wealth and power in fewer and fewer hands"--